A novel membrane-bound interleukin-2 promotes NK-92 cell persistence and anti-tumor activity. (31st December 2022) - Xiong, Qi; Zhang, Hantao; Ji, Xuanle; Zhang, Yong; Shi, Gang; Dai, Lei; Cheng, Fuyi; Wang, Huiling; Luo, Jieyan; Xu, Jia; Ji, Yanhong; Su, Xiaolan; et al.
ABSTRACT: A major challenge in natural killer (NK) cell immunotherapy is the limited persistence of NK cells in vivo . However, the proliferation of NK cells is dependent on cytokines such as interleukin-2 (IL-2). Although IL-2 is a critical cytokine for NK cell activation and survival, IL-2 administration in adoptive NK cell therapy can induce adverse toxicities. To improve the persistence of NK cells and attenuate the systemic toxicity of IL-2, we constructed a cell-restricted artificial IL-2, named membrane-bound IL-2 (mbIL-2), comprising human IL-2 and human IL-2Rα joined by a classic linker. We found that mbIL-2-activated NK-92 cells can survive and proliferate in vitro and in vivo, independent of exogenous IL-2, while mbIL-2-expressing NK-92 cells do not support bystander cell survival or proliferation. Additionally, mbIL-2 enhanced NK-92 cell-mediated antitumor activity by tuning the IL-2 receptor downstream signals and NK cell receptor repertoire expression. To conclude, our novel mbIL-2 improves NK-92 cell persistence and enhances NK-92 cell-mediated antitumor activity. NK-92 cells genetically modified to express the novel mbIL-2 with potential significance for clinical development.